Mesentéric Segmentary Thrombosis. Atipical Presentation. Clinical Case - Flores-López, Alejandro Alberto; Padrón-Arredondo, Guillermo; Yépez-Vallejo, Segundo; Cruz-Méndez, Adriana Teresa; Rodriguez-Perera, Jacob; Gómez-Salazar, Adriana Guadalupe; Agustín-Martínez, Alejandro; Falcón-Cancino, Luis Arturo; Espinosa-Rosales, Alicia Valeria; Villalobos-Rodríguez, Alejandro L. (British Journal of Healthcare and Medical Research, 2023)
Introduction: No occlusive mesenteric ischemia was first reported by Ende et al., in 1958 as a syndrome of small intestinal necrosis in patients with heart failure subsequently, hypoperfusion of the intestines due to various factors induces mesenteric vascular spasm. Clínical Case: A 74-year-old female was admitted to the Emergency Department due to jaundice, intolerance to the oral route, and hemodynamic instability, Septic Shock of abdominal origin secondary to Cholangitis secondary to Choledocholithiasis. After 72 h, she was discharged from the Intensive Care Unit due to improvement to continue surveillance in the General Surgery Hospitalization. During his stay on the floor of General Surgery, she again presented intolerance to the oral intake, abdominal distension, and clinical deterioration, for which a Tomography of the Abdomen was performed, finding significant distension of the small bowel loops from the distal ileum secondary to two circular hyperdense images of 14 and 16 mm located 3.2 cm proximal to the ileocecal valve, as well as free fluid in the cavity, for which it was decided to perform Exploratory Laparotomy with the following findings: Two stones with pigmented biliary characteristics located 3 cm from the ileocecal valve of 1.5 cm each one, segmental mesenteric ischemia of approximately 60 cm in the terminal ileum, ascites 400 cc of purulent yellow fluid, multiple loose liver-omentum-transverse colon adhesions; 60 cm resection of the terminal ileum + ileostomy is performed. In the postoperative period, the patient was admitted to the Intensive Care Unit where she evolved favorably until her hospital discharge. Discussion: Medical patients are often admitted to the ICU for the management of septic or hypovolemic Shock or respiratory failure. Although recent clinical practice guidelines recommend light sedation for patients in the ICU, some patients require deep sedation during the initial phase of ICU management. Therefore, for medical ICU patients, early evaluation of abdominal symptoms might be difficult. In addition, physicians often overlook the monitoring of abdominal symptoms in medical patients, which can lead to a delayed NOMI diagnosis and an increase in mortality.